Social Problems in Short Stories entitled Mata Yang Enak Dipandang by Ahmad Tohari and its Relevance in Senior High School - Agus Yuliyanto; Suyitno Suyitno; Muhammad Rohmadi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This research was based on the view that literature is basically a reflection of society. So in this study, researchers used the approach to the sociology of literature. This paper aimed to describe (1) short story becomes one of the literary works that are used as teaching material in schools, (2) the aspect of characrter education based on the collection of short stories entitled Mata Yang Enak Dipandang by Ahmad Tohari, and (3) social problems collection of short stories entitled Mata Yang Enak Dipandang. The method used in this research is qualitative descriptive explaining the data that has been found in research. The main data sources in this study the quotations contained in the novel and the results of interviews with literary experts and learning experts. The results of this study is the main characters in this short story are varied and its can be utilized in the study of literary appreciation for Class XI in Senior high school semester with the standard literary discourse understanding competence through reading poetry and short stories in the aspects of reading and basic competence that is analyzing the intrinsic elements of a short story linkages with everyday life